Osteomeles schwerinae Extract Prevents Diabetes-Induced Renal Injury in Spontaneously Diabetic Torii Rats. (24th April 2018) - Sohn, Eunjin; Kim, Junghyun; Kim, Chan-Sik; Jo, Kyuhyung; Kim, Jin Sook
Abstract : Mesangial cell proliferation contributes to the development of glomerulosclerosis in diabetic nephropathy. This study was aimed at determining whether Osteomeles schwerinae (OSSC) extract can ameliorate renal damage in Spontaneously Diabetic Torii (SDT) rats. OSSC extract (100 and 250 mg/kg/day) was administered to the SDT rats through oral gavage for 17 weeks. At the end of the experiment, glucose, HbA1c, and albuminuria were measured. In addition, the levels of mesangial proliferation-related proteins were determined by western blotting and immunohistochemistry. Our results show that albuminuria, accumulation of the extracellular matrix (ECM), and renal expansion were markedly restored by OSSC extract administration. The OSSC treatment also inhibited α -smooth muscle actin and transforming growth factor- β 1 protein expression. In addition, OSSC and its bioactive compounds hyperoside and quercitrin inhibited the platelet-derived growth factor-BB (PDGF-BB)/platelet-derived growth factor-B receptor (PDGFR- β ) ligand binding in an in vitro assay. Taken together, these results indicate that OSSC inhibits ECM accumulation and mesangial proliferation of the glomeruli in SDT rats through inhibition of the interaction between PDGF-BB and PDGFR- β . OSSC has ameliorating effects on the initiation and progression of diabetes complications and can be used for the treatment of early diabetic renal dysfunction.